(untitled) - Kottak, Conrad Phillip (Boston, 2009)
Contents: Introduction to anthropology; What is anthropology?; Applying anthropology; Studying the past; Evolution and genetics; Human variation and adaptation; The primates...
Keywords: Anthropology,Nhân chủng học